Colombian indigenous culture affected by the government inclusion policies (2016)
The present literature review has as a main object to identify and analyze the alteration caused by the Colombian government inclusion policies over the indigenous culture of the country, based on historical events concerning about the American discovery and conquest, as well as the colonization of the Colombian indigenous population. The purpose of this research is to expose the different losses or changes that these communities have suffered, creating a social inquiry regarding the treatment that our indigenous cultures are receiving, and how this is degrading the autochthonous Colombian culture.